A development plan for the establishment of a library for the Our Lady of Banneux (OLB) community in San Mateo, Rizal - Ibal, Nicole Noelle P. (2018)
This paper documents the processes in building the Our Lady of Banneux Community Library and its collection. It focuses on the preparations and development planning of the community library. This shares the experiences and practices relating to the different library policies and three (3) year development plan for building the library of Our Lady of Banneux (OLB) Community. The development plan consists of the vision, mission, goals and objectives of the library, building and maintaining its collection, general rules and regulations, and the timeline of the activity. Building the library of Our Lady of Banneux (OLB) Community, so far, has had fruitful results due to the development plan. The plan is expected to provide a good framework in developing the library operations in the long run.